Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.

Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.
Keywords: climatic gradient; community; nomenclature; obligate seeder; resilience; resprouter; Seeder